(untitled) - Boylestad, Robert (Englewood Cliffs, NJ, 1987)
This text is designed primarily for use in a two-semester or three-trimester sequence in the basic electronics area. It is expected that the student has taken a course in dc circuit analysis and has either taken or is taking a course in ac circuit analysis.
Mạch điện tử
Keywords: Electronic circuits,Electronic apparatus and appliances,Mạch điện,Máy móc và thiết bị điện tử